RETRACTED: Phonetic articulation of Russian noise consonants produced by Chinese-speaking students - Semenova Marina; Atamas Anastasia; Jinhui Jiang (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001